Public relations - Blythe, James (Henry Stewart Talks, 2012)
Role of PR officers, Tools of PR, Examples of good PR, PR and staff, Internal PR, Tools of PR, PR and the media, Writing a press release, Organising a press conference, PR and shareholders, PR and Government, PR and external pressure groups, PR and electronic media, Word of mouth, Product placement, Sponsorship, Handling criticism: defensive PR, Influencing opinion: proactive PR, Crisis management, Corporate image advertising, PR in a global context, What PR will and will not do